INTERNALIZATION OF CRITICAL DIALOGUE EDUCATION IN THE STORIES OF PROPHET KHIDIR AND PROPHET MUSA: ANALYSIS OF VALUES AND RELEVANCE IN CHARACTER EDUCATION - Husna, Aviah Asmaul; BZ, Zakiyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Education plays a crucial role in shaping human character, not only in terms of knowledge but also in moral, emotional, social, and spiritual dimensions. Islamic education's primary goal is not only to transfer knowledge but also to instill good moral values and ethics, as taught by Prophet Muhammad in QS. Al-Qalam: 68, verse 4. This research aims to analyze the educational values contained in the story of Prophet Khidir and Prophet Musa in Surah Al-Kahfi verses 60-82, which can be applied in the formation of students' character. The story portrays the dialogue between Prophet Musa and Prophet Khidir, which holds significant meaning in the process of reflective education based on moral values. In this story, Prophet Musa seeks to understand the wisdom and lessons conveyed by Prophet Khidir, who serves as a model of learning that emphasizes patience, sincerity, humility, and social responsibility. These values are highly relevant in character education, where the main objective is not only to transfer knowledge but also to form a strong and moral personality. The research method used is a literature review with a descriptive-qualitative approach and content analysis of literature related to character education and Islamic pedagogy. The findings indicate that the character education model based on critical dialogue, exemplified in the story of Prophet Musa and Prophet Khidir, can shape individuals who think critically, understand social contexts, and have moral responsibility. This model offers an approach that combines reflection-based learning with modern Islamic pedagogy, which is relevant to contemporary educational challenges. By implementing these values into the character education curriculum, a holistic personality can be developed, encompassing intellectual, emotional, social, and moral aspects. This story teaches that true education involves a deep understanding of destiny and wisdom and trains individuals to act with integrity and care for the welfare of society.